Development and validation of a natural dynamic facial expression stimulus set - Borges Bastos Pasqualette, Laura Beatriz; Klinger, Sara; Kulke, Louisa (PLoS ONE, 2023)
Emotion research commonly uses either controlled and standardised pictures or natural video stimuli to measure participants’ reactions to emotional content. Natural stimulus materials can be beneficial; however, certain measures such as neuroscientific methods, require temporally and visually controlled stimulus material. The current study aimed to create and validate video stimuli in which a model displays positive, neutral and negative expressions. These stimuli were kept as natural as possible while editing timing and visual features to make them suitable for neuroscientific research (e.g. EEG). The stimuli were successfully controlled regarding their features and the validation studies show that participants reliably classify the displayed expression correctly and perceive it as genuine. In conclusion, we present a motion stimulus set that is perceived as natural and that is suitable for neuroscientific research, as well as a pipeline describing successful editing methods for controlling natural stimuli.
CRIS-Team Scopus Importer:2023-07-21

Effects of emotional content on social inhibition of gaze in live social and non-social situations - Kulke, Louisa; Borges Bastos Pasqualette, Laura Beatriz (Scientific Reports, 2023)
Abstract: In real-life interactions, it is crucial that humans adequately respond to others’ emotional expressions. Emotion perception so far has mainly been studied in highly controlled laboratory tasks. However, recent research suggests that attention and gaze behaviour significantly differ between watching a person on a controlled laboratory screen compared to in real world interactions. Therefore, the current study aimed to investigate effects of emotional expression on participants’ gaze in social and non-social situations. We compared looking behaviour towards a confederate showing positive, neutral or negative facial expressions between live social and non-social waiting room situations. Participants looked more often and longer to the confederate on the screen, than when physically present in the room. Expressions displayed by the confederate and individual traits (social anxiety and autistic traits) of participants did not reliably relate to gaze behaviour. Indications of covert attention also occurred more often and longer during the non-social, than during the social condition. Findings indicate that social norm is a strong factor modulating gaze behaviour in social contexts. Protocol registration: The stage 1 protocol for this Registered Report was accepted in principle on September 13, 2021. The protocol, as accepted by the journal, can be found at: https://doi.org/10.6084/m9.figshare.16628290 .
CRIS-Team Scopus Importer:2023-09-08

Emotional content influences eye-movements under natural but not under instructed conditions - Kulke, Louisa; Borges Bastos Pasqualette, Laura Beatriz (Cognition & Emotion, 2021)
In everyday life, people can freely decide if and where they would like to move their attention and gaze, often influenced by physical and emotional salience of stimuli. However, many laboratory paradigms explicitly instruct participants when and how to move their eyes, leading to unnatural instructed eye-movements. The current preregistered study compared eye-movements to peripherally appearing faces with happy, angry and neutral expressions under natural and instructed conditions. Participants reliably moved their eyes towards peripheral faces, even when they were not instructed to do so; however, eye-movements were significantly slower under natural than under instructed conditions. Competing central stimuli decelerated eye-movements independently of instructions. Unexpectedly, the emotional salience only affected eye-movements under natural conditions, with faster saccades towards emotional than towards neutral faces. No effects of emotional expression occurred when participants were instructed to move their eyes. The study shows that natural eye-movements significantly differ from instructed eye-movements and emotion-driven attention effects are reduced when participants are artificially instructed to move their eyes, suggesting that research should investigate eye-movements under natural conditions.
CRIS-Team WoS Importer:2021-12-24

Self-Relevance Predicts the Aesthetic Appeal of Real and Synthetic Artworks Generated via Neural Style Transfer - Vessel, Edward A.; Borges Bastos Pasqualette, Laura Beatriz; Uran, Cem; Koldehoff, Sarah; Bignardi, Giacomo; Vinck, Martin (Psychological Science, 2023)
What determines the aesthetic appeal of artworks? Recent work suggests that aesthetic appeal can, to some extent, be predicted from a visual artwork’s image features. Yet a large fraction of variance in aesthetic ratings remains unexplained and may relate to individual preferences. We hypothesized that an artwork’s aesthetic appeal depends strongly on self-relevance. In a first study (N = 33 adults, online replication N = 208), rated aesthetic appeal for real artworks was positively predicted by rated self-relevance. In a second experiment (N = 45 online), we created synthetic, self-relevant artworks using deep neural networks that transferred the style of existing artworks to photographs. Style transfer was applied to self-relevant photographs selected to reflect participant-specific attributes such as autobiographical memories. Self-relevant, synthetic artworks were rated as more aesthetically appealing than matched control images, at a level similar to human-made artworks. Thus, self-relevance is a key determinant of aesthetic appeal, independent of artistic skill and image features.
CRIS-Team Scopus Importer:2023-09-08
Keywords: aesthetic valuation; artwork; identity; machine learning; open data